2020
DOI: 10.3390/ma13071494
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication, Modeling and Characterization of Magnetostrictive Short Fiber Composites

Abstract: Magnetostrictive materials have a wide variety of applications due to their great capability as sensors and energy-harvesting devices. However, their brittleness inhibits their applications as magnetostrictive devices. Recently, we developed a continuous magnetostrictive Fe-Co-fiber-embedded epoxy matrix composite to increase the flexibility of the material. In this study, we fabricated random magnetostrictive Fe-Co short fiber/epoxy composite sheets. It was found that the discontinuous Fe-Co fiber composite s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 21 publications
1
12
0
1
Order By: Relevance
“…Tahap optimasi geometri senyawa Andrographolide dan Dendronpholide G dilakukan dengan menggunakan software HyperChem Professional 8.0. Optimasi geometri ini bertujuan untuk memperoleh konfirmasi stuktur yang sebenarnya dengan metode semi empiris AM1 (Wang et al, 2020).…”
Section: Optimasi Geometri Senyawa Ujiunclassified
“…Tahap optimasi geometri senyawa Andrographolide dan Dendronpholide G dilakukan dengan menggunakan software HyperChem Professional 8.0. Optimasi geometri ini bertujuan untuk memperoleh konfirmasi stuktur yang sebenarnya dengan metode semi empiris AM1 (Wang et al, 2020).…”
Section: Optimasi Geometri Senyawa Ujiunclassified
“…In recent years, it was shown that the embedding of the FeCo wires in a polymer matrix leads to magnetostrictive composite materials with enhanced inverse magnetostrictive effect. [ 15–19 ]…”
Section: S 33 M [× 10−12 M2 N−1] S 33 F [× 10−12 M2 N−1] mentioning
confidence: 99%
“…[ 25 ] Meanwhile, magnetostrictive materials can convert magnetic energy into mechanical energy or the reverse, [ 26,27 ] and are used to build sensors and actuators. In the past decade, works on magnetostrictive alloys and composites, including clad plates, [ 28 ] short wire composites, [ 29 ] and long wire composites, [ 30 ] have been reported by our group. A new type of active magnetostrictive material has also been introduced as a biological sensor platform [ 31 ] in recent years.…”
Section: Introductionmentioning
confidence: 99%